2014
DOI: 10.1289/ehp.1307518
|View full text |Cite|
|
Sign up to set email alerts
|

A Unique Co-culture Model for Fundamental and Applied Studies of Human Fetoplacental Steroidogenesis and Interference by Environmental Chemicals

Abstract: Background: Experimental tools for studying the complex steroidogenic interactions that occur between placenta and fetus during human pregnancy are extremely limited.Objectives: We aimed to develop a co-culture model to study steroidogenesis by the human fetoplacental unit and its disruption by exposure to environmental contaminants.Methods: We cultured BeWo human choriocarcinoma cells, representing the villous cytotrophoblast, and H295R human adrenocortical carcinoma cells, representing the fetal unit, in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Effects on aromatase and consequences for human health are less well understood. It has been demonstrated that exposure to atrazine, a widely used herbicide, induces aromatase expression and estrogen biosynthesis in certain human cell lines (Sanderson et al, 2001(Sanderson et al, , 2002Thibeault et al, 2014), but the effects of chemicals on the promoter-and tissue-specific expression of aromatase are largely unknown. In placenta, CYP19 is expressed mainly via the placenta-specific promoter I.1, and the estrogens produced are essential for proper development of placenta and fetus (Albrecht and Pepe, 2010;Bukovsky et al, 2003).…”
mentioning
confidence: 99%
“…Effects on aromatase and consequences for human health are less well understood. It has been demonstrated that exposure to atrazine, a widely used herbicide, induces aromatase expression and estrogen biosynthesis in certain human cell lines (Sanderson et al, 2001(Sanderson et al, , 2002Thibeault et al, 2014), but the effects of chemicals on the promoter-and tissue-specific expression of aromatase are largely unknown. In placenta, CYP19 is expressed mainly via the placenta-specific promoter I.1, and the estrogens produced are essential for proper development of placenta and fetus (Albrecht and Pepe, 2010;Bukovsky et al, 2003).…”
mentioning
confidence: 99%
“…Two additional stress-related CPs, HIF1A signaling and UVA-induced MAPK signaling, were affected. For comparison, past studies reported that ATR at 60 nM inhibits mouse T-cell proliferation [57], whereas 30 μM ATM does not inhibit proliferation but induces CYP19 activity in human placental cells [43]. …”
Section: Resultsmentioning
confidence: 99%
“…The concentration of ATR used was ~4-fold higher than the maximum concentration reported in one study in drinking water [36], and one study of occupational human serum level (up to 245 nM [42]). The ATR concentration used affects placenta cell gene expression in vitro [43] and is much lower than the doses (200–300 mg/kg) typically applied in rodent studies to test for reproductive effects. Some of these chemicals exert effects on rhesus monkey gonads, embryo or fetal development, and progeny phenotype, or in human reproductive tissues or stem cells.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to atrazine, a widely used herbicide, induces CYP19 expression, aromatase activity and estrogen biosynthesis in human cell lines [12,13,14,15,16] , but little is known about "emerging" contaminants such as neonicotinoid insecticides. Neonicotinoids are the most commonly used insecticides worldwide, and are applied as coatings to the seeds of corn, canola, soybeans and the majority of fruits and vegetables.…”
Section: Research Highlightmentioning
confidence: 99%